Strong-field control of H3+ production from methanol dications: Selecting between local and extended formation mechanisms - Iwamoto, Naoki; Schwartz, Charles J.; Jochim, Bethany; Raju P., Kanaka; Feizollah, Peyman; Napierala, J. L.; Severt, T.; Tegegn, S. N.; Solomon, A.; Zhao, S.; Lam, Huynh; Wangjam, Tomthin Nganba; et al. (My University, 2020)
Using the CD3OH isotopologue of methanol, the ratio of D2H+ to D3+ formation is manipulated by changing the characteristics of the intense femtosecond laser pulse. Detection of D2H+ indicates a formation process involving two hydrogen atoms from the methyl side of the molecule and a proton from the hydroxyl side, while detection of D3+ indicates local formation involving only the methyl group. Both mechanisms are thought to involve a neutral D2 moiety. An adaptive control strategy that employs image-based feedback to guide the learning algorithm results in an enhancement of the D2H+/D3+ ratio by a factor of approximately two. The optimized pulses have secondary structures 110–210 fs after the main pulse and result in photofragments that have different kinetic energy release distributions than those produced from near transform limited pulses. Systematic changes to the linear chirp and higher order dispersion terms of the laser pulse are compared to the results obtained with the optimized pulse shapes.